Polarization Electric Field Inside Auroral Patches: Simultaneous Experiment of EISCAT Radars and KAIRA. Issue 5 (8th May 2019) - Takahashi, Toru; Virtanen, Ilkka I.; Hosokawa, Keisuke; Ogawa, Yasunobu; Aikio, Anita; Miyaoka, Hiroshi; Kero, Antti
Abstract: The primary focus of this study was the motion of auroral patches and the polarization electric field generated therein observed on 9 November 2015 in an experiment using the European incoherent scatter (EISCAT) radars, Kilpisjärvi Atmospheric Imaging Receiver Array (KAIRA), and an all‐sky imager simultaneously. Based on the all‐sky imager data, the drift speed of the auroral patches corresponded to a southward electric field of 14.1( ± 3.7)–17.2( ± 4.5) mV/m. The convective electric field derived from the EISCAT radars and KAIRA observation was approximately 14.6 mV/m in the southward direction. This suggest that the spatial distribution of the auroral patches reflects the distribution of the cold plasma in the magnetosphere. The electron density and the height‐integrated Hall conductance between 80 and 120 km were enhanced by a factor of 2–4 inside the auroral patches. In this situation, a polarization electric field was generated therein. Enhanced ion velocities due to the polarization electric field was observed at up to 200‐km altitude; however, the absolute values of the ion velocities were approximately 40% of what was expected from the polarization electric field. A field‐aligned current (FAC) from 5 to 10 μA/m −2 in the edges of the auroral patches could explain the weakening of the polarization electric field. Since a FAC of that order of magnitude corresponded with that observed by the Swarm satellite, it was suggested that the polarization electric field was weakened by the FAC. Furthermore, the polarization electric field propagated upward from the dynamo region to at least 200 km. Key Points: The drift speed of auroral patches was consistent with the convective electric field The polarization electric fields perpendicular to the convective electric fields were generated inside the auroral patches The upward and downward FACs contacting the west and east side edges of the auroral patches weakened the polarization electric field